GLP-1 receptor agonist for weight loss and fertility: Social media and online perception versus evidence-based medicine. - Zaher Merhi; Manasi Karekar; Marco Mouanness (PLoS ONE)
Background The injectable glucagon-like peptide-1 (GLP-1) receptor agonist (RA) drugs are commonly used for weight loss among reproductive-aged women but the perception of their impact on fertility is not clear among the public. Objectives The purpose of this review was to compare scientific literature to social media discourse and online search pertaining to the potential impact of GLP-1 RAs on female fertility. Methods Group 1 included 3 social media platforms, each of which required a different data collection method. For Reddit, VADER (Communalytic ®) was used as a sentiment analyzer and for Twitter and TikTok, we performed a manual search for posts and scored them using an objective internal scale. Group 2 included the online search engine Google Trends. Group 3 consisted of medical literature search by PubMed. All sentiments of posts/comments/articles were graded as: "Positive, Neutral, or Negative" and compared among groups. Results In Groups 1 and 2, scores showed a significantly more Positive than Neutral, and more Neutral than Negative sentiments. In Group 3, among the 52 original studies found on PubMed in women with polycystic ovary syndrome (PCOS), they all had Positive sentiments. In Groups 1, 2, and 3, there was a strong positive correlation among all sentiments (r2 = 0.83). Even though all 3 social media platforms had the majority of posts with a Positive sentiment and correlated with Google Trends posts and with PubMed studies in women with PCOS (r2 = 0.74), there was a lack of PubMed studies pertaining to the effect of GLP-1 RA in women without PCOS. Conclusion The Positive sentiments among women without PCOS is not justified by evidence-based medicine and there is a clear need for studies pertaining to this topic.